Increasing speaking Ability through YouTube video for Engineering Students at Sekolah Tinggi Teknologi Pekanbaru - Amsa, Helfany; Junaidi, Abdul Khair; Franchisca, Sherly; Astuti, Indri; Burhan, Kristian (English Education Study Program FKIP Universitas Alwashliyah Medan, 2024)
The focus of the research is the use of YouTube as a learning media in English classes for mechanical engineering students. The purpose of using YouTube videos is to improve students' speaking skills and create a comfortable classroom environment, and increase students' enthusiasm for learning in class. This study uses a descriptive qualitative approach. Students speak with more confidence and are more expressive as a result of the highly effective use of YouTube media in the classroom. In addition, students do not need to worry about the phrases they use when speaking English because they have already witnessed how foreigners speak fluently and correctly.